Investigation of the Optimum Clocking Position in a Two-Stage Axial Turbine - Dieter Bohn; Sabine Ausmeier; Jing Ren (International Journal of Rotating Machinery)
A frozen rotor approach in a steady calculation and a sliding mesh approach in an unsteady simulation are performed in a stator clocking investigation. The clocking is executed on the second stator in a two-stage axial turbine over several circumferential positions. Flow field distributions as well as the estimated performances from two approaches are compared with each other. The optimum clocking positions are predicted based on the estimated efficiency from the two approaches. The consistence of the optimum clocking positions is discussed in the paper. The availability and the limit of the frozen rotor approach in predicting the optimum clocking position is analyzed. It is concluded that the frozen rotor approach is available to search the optimum clocking position in the preliminary design period, although it misses some features of the unsteady flow field in the multistage turbines.